2021
DOI: 10.3389/fonc.2021.629132
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Herbal Medicines Intervention for Colorectal Cancer Patients With Chemotherapy-Induced Gastrointestinal Toxicity — a Systematic Review and Meta-Analysis

Abstract: Purpose: Chemotherapy-induced gastrointestinal (CIGI) toxicity affects the quality of life of patients with colorectal cancer (CRC) and the clinical application of treatment drugs. This review aims to evaluate the efficacy of traditional herbal medicines (HMs) in alleviating symptoms of CIGI toxicity (including nausea and vomiting, anorexia, diarrhea, constipation, oral mucositis, abdominal pain, and abdominal distension), and to explore further individual herb or herbal combinations in alleviating the CIGI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…( 53 ) and Chen Y et al. ( 54 ). All significant RR results were shown in Tables 6A and 6B , and only the RRs with low heterogeneity (I 2 < 30%) that were not greater than the total pooled RR were shown in the text.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…( 53 ) and Chen Y et al. ( 54 ). All significant RR results were shown in Tables 6A and 6B , and only the RRs with low heterogeneity (I 2 < 30%) that were not greater than the total pooled RR were shown in the text.…”
Section: Resultsmentioning
confidence: 97%
“…SD, standard deviation; KPS, Karnofsky Performance Status; TMPs, traditional medicine preparations; E/C, experimental group (TMPs combined with chemotherapy)/control group (chemotherapy alone); M/F, male/female; BSA, body surface area; O, outcome; O1, tumor response; O2, quality of life (QOL); O3, the cancer biomarkers; O4, adverse drug reactions (ADRs).analysis was conducted based on the specific ingredients of TMPs from each study listed in Table1according to the method described in Chen MH, et al(53) and Chen Y et al(54). All significant RR results were shown in Tables6A and 6B, and only the RRs with low heterogeneity (I 2 < 30%) that were not greater than the total pooled RR were shown in the text.…”
mentioning
confidence: 99%
“…As previous described [ 49 , 50 ], a subgroup analysis was conducted on particular components of ginseng-containing preparations from each trial, as listed in Table 1 , to determine the combination of ginseng and other herbs with FBC with the most contribution to AGC treatment. Tables 5 and 6 only include RRs that had a low heterogeneity ( I 2 < 30%) and were less than the overall pooled RR.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, it has gained traction as a treatment option for patients with CIBP. Studies have shown that astragalus, psoralen, scutellaria barbata, atractylodes macrocephala, and corydalis can significantly inhibit CIBP in patients with cancer ( 82 85 ). Insect drugs, such as scorpion and Huchansu have also been shown to be effective for the management of CIBP ( 86 – 88 ).…”
Section: Pain Management Of Bone Metastasesmentioning
confidence: 99%